2021
DOI: 10.3390/jcm10092002
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Bracket Placement with an Indirect Bonding Method Using Digitally Designed Transfer Models Printed in Different Orientations—An In Vitro Study

Abstract: Objective: A digital workflow opens up new possibilities for the indirect bonding (IDB) of brackets. We tested if the printing orientation for bracket transfer models on the build platform of a 3D printer influences the accuracy of the following IDB method. We also evaluated the clinical acceptability of the IDB method combining digitally planned and printed transfer models with the conventional fabrication of pressure-molded transfer trays. Materials and Methods: In total, 27 digitally planned bracket transfe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In the literature, different procedures for digitizing study models, e.g., intraoral scanners, 3D-model scanners or cone beam computed tomography (CBCT), were described for assessing the accuracy of transfer trays in digital workflows [29][30][31][32]. Matching intraoral scans (IOS) with the virtually planned reference models seems to be used most frequently and has the advantage that this workflow can be easily applied to clinical as well as in vitro settings, whereas microcomputed tomography (micro-CT) is limited to in vitro studies only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, different procedures for digitizing study models, e.g., intraoral scanners, 3D-model scanners or cone beam computed tomography (CBCT), were described for assessing the accuracy of transfer trays in digital workflows [29][30][31][32]. Matching intraoral scans (IOS) with the virtually planned reference models seems to be used most frequently and has the advantage that this workflow can be easily applied to clinical as well as in vitro settings, whereas microcomputed tomography (micro-CT) is limited to in vitro studies only.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the amount of deviations, linear discrepancies ≤ 0.5 mm and angular deviations of ≤2 • were considered to be acceptable as suggested by The American Board of Orthodontists (ABO) [37] and further studies [21,32], despite some authors recommending more strict ranges [30,38].…”
Section: Discussionmentioning
confidence: 99%
“…Grünheid et al reported that the anterior teeth (−0.012 ± 0.009 mm in mesio-distal measures, 0.026 ± 0.013 mm in vertical measures, and 0.0103° ± 0.085, 0.061° ± 0.005, and 0.235° ± 0.010 for the torque, tip, and rotation, respectively) showed more accurate indirect bonding positions of the fixed multibracket appliances than the posterior teeth did (−0.063 ± 0.033 mm in mesio-distal measures, 0.035 ± 0.017 mm in vertical measures, and −0.268° ± 0.520, −0.213° ± 0.445, and 0.405° ± 0.335 for the torque, tip, and rotation, respectively) [ 19 ]. Süpple et al found more displacement in the molar teeth 21, and Kim et al reported this discrepancy in the posterior teeth in the height of the cusps [ 20 ]. However, in the present study, this result was found just in the mesio-distal measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating gluconic acid with hydrogel wound dressings stabilizes the pH ranges that are significant for bacterial protection. For instance, maintaining wound pH in the range of 3.2–4.5 by use of gluconic acid, creates an environment that prevents pathogen growth [ 225 ]. In addition, gluconic acid may enhance environmental moisture, and reduce inflammation and infection [ 225 ].…”
Section: Fundamental Challenges and Future Outcomesmentioning
confidence: 99%
“…For instance, maintaining wound pH in the range of 3.2–4.5 by use of gluconic acid, creates an environment that prevents pathogen growth [ 225 ]. In addition, gluconic acid may enhance environmental moisture, and reduce inflammation and infection [ 225 ]. Adding nanofiller to the hydrogel makes transporting active agents, such as drugs, feasible by moving in and out of skin via diffusion and active transport.…”
Section: Fundamental Challenges and Future Outcomesmentioning
confidence: 99%